Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1177/0300060519862957
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of basicervical femoral neck fractures with proximal femoral nail antirotation

Abstract: Objective A basicervical femoral neck fracture, which is located at the junction between the femoral neck and intertrochanteric region, is a rare type of fracture. The treatment effects for this type of fracture vary. The present retrospective study was performed to evaluate the clinical and radiological outcomes of proximal femoral nail antirotation and illustrate its effect on improving the clinical prognosis of basicervical femoral neck fractures. Methods Fourteen patients with two-part basicervical fractur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 22 publications
0
23
0
1
Order By: Relevance
“…Guo et al 16) (2019) A basicervical femoral neck fracture, which is located at the junction between the femoral neck Not mentioned.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Guo et al 16) (2019) A basicervical femoral neck fracture, which is located at the junction between the femoral neck Not mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…However, Massoud 3) have suggested that an anti-rotational screw should be added to control rotational instability after surgery because the lag screw has potential to rotate the rotationally unstable femoral head during its insertion. Authors of recent reports included in this study argue that the antirotational effect of implant should be taken into account when selecting an implant for the fixation of these rotationally unstable fractures [14][15][16][17][18][19] .…”
Section: Ota/ao: A1mentioning
confidence: 99%
See 3 more Smart Citations